1989
DOI: 10.1097/00000658-198908000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of the Portal Vein

Abstract: A 14-year-old girl presented at the hospital after discovering an abdominal tumor. CT scan and ultrasonography indicated a hepatic tumor and also revealed the absence of the portal vein. The patient was admitted to excise the hepatic tumor. It was found that the venous blood from the small intestines flowed into the left renal vein and then emptied directly into the inferior vena cava. A tumor extending from the right lobe through the middle portion of the liver was excised. The postoperative course was satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 4 publications
1
66
0
1
Order By: Relevance
“…That is, hyperammonemia induced encephalopathy regardless of age. Nakasaki et al (16) reported that production of ammoniawas suppressed in the intestine as homeostasis in a case of congenital absence of the portal vein. They investigated the patient' s intestinal bacterial flora, and discovered distinct differences from the normal flora with respect to both varieties and numbers of the intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…That is, hyperammonemia induced encephalopathy regardless of age. Nakasaki et al (16) reported that production of ammoniawas suppressed in the intestine as homeostasis in a case of congenital absence of the portal vein. They investigated the patient' s intestinal bacterial flora, and discovered distinct differences from the normal flora with respect to both varieties and numbers of the intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…Several patients have been found to have combined hepatocellular adenoma [31,36,37] . These are generally considered benign parenchymatous lesions, and also have the potential to deteriorate into hepatoblastoma [26,28] and hepatocellular carcinoma (HCC) [12,20,38,39] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Congenital cardiac diseases including atrial septal defect (ASD) [2,21,26,28,37,44,45] or patent foramen ovale [43] , ventricular septal defect (VSD) [16,17,21,26,31,40] , and patent ductus arterious (PDA) [12,23,43,44] are frequently observed along with CAPV. Bellah et al [45] have also detected a fatal congenital hypertrophic cardiomyopathy with ultrasound in an infant.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations